2020
DOI: 10.1021/acs.orglett.9b04215
|View full text |Cite
|
Sign up to set email alerts
|

DFT Mechanistic Account for the Site Selectivity of Electron-Rich C(sp3)–H Bond in the Manganese-Catalyzed Aminations

Abstract: DFT study suggests that the C–H cleavage involved in the C­(sp3)–H amination catalyzed by manganese perchlorophthalocyanine complex [MnIII(ClPc)]+ proceeds via hydride transfer (HYT), instead of hydrogen atom transfer (HAT), thus elucidating why the reaction favors aminating the electron-rich C–H bond, rather than that with smaller bond dissociation energy preferred by HAT. Detailed analyses indicate the HYT actually occurs via concerted electron and hydrogen atom transfers and the redox-active ClPc ligand ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 82 publications
2
9
0
Order By: Relevance
“…The charge and spin density of the quintet state 5 INT3a / 5 INT3b also agree with their diradical character, and that of the quintet state 5 INT4 agree with its zwitterionic character. These results support that INT4 and INT3a / INT3b are formed through different mechanisms . Therefore, a tetrahedral σ-intermediate INT4 is formed via the electrophilic attack of Mn–oxo species INT2 to aromatic ring in OAT mechanism .…”
Section: Results and Discussionsupporting
confidence: 74%
“…The charge and spin density of the quintet state 5 INT3a / 5 INT3b also agree with their diradical character, and that of the quintet state 5 INT4 agree with its zwitterionic character. These results support that INT4 and INT3a / INT3b are formed through different mechanisms . Therefore, a tetrahedral σ-intermediate INT4 is formed via the electrophilic attack of Mn–oxo species INT2 to aromatic ring in OAT mechanism .…”
Section: Results and Discussionsupporting
confidence: 74%
“…Hence, there is an urgent need for a deep understanding of the mechanism and different selectivity at the molecular level in this type of emerging organic reactions. Presently, computational chemistry not only contributes to our current understanding of the basic reactions in organic chemistry but also is particularly helpful in analyzing the physical factors that control different selectivity of organic chemical reactions . With an objective to better understand the origins of the chemo-, regio-, and stereoselectivity in these intriguing transformations (Scheme ) and contribute to the development of new strategies for other catalyst-controlled organic synthesis reactions, we have performed an exhaustive DFT calculation study aiming at investigating the unique selectivity achieved in the presence of different catalytic systems.…”
supporting
confidence: 75%
“…This is consistent with the recent study on the Mn III (ClPc) + -catalyzed electron-rich C(sp 3 )−H amination reported by Wang and co-workers. 42 Thus, we believe that the anion effect can be safely ignored.…”
Section: Resultsmentioning
confidence: 96%